Impacts of Social Forestry on Land Cover in Makarti Jaya District, Banyuasin Regency : Dampak Persetujuan Pengelolaan Perhutanan Sosial Terhadap Penutupan Lahan di Kecamatan Makarti Jaya Kabupaten Banyuasin - Ahmad Zamhari; Jun Harbi (Universitas Muhammadiyah Palembang, 2025)
Social forestry is a national priority program aimed at providing legal access to communities in managing forest areas to resolve tenure conflicts and improve community welfare. Since its implementation in 2016, evaluating its impact has become important, especially regarding land cover changes. This study aims to analyze the impact of social forestry approval on land cover in Makarti Jaya District, Banyuasin Regency. This research was conducted in December 2024 using the visual delineation method through on-screen digitization of Google Earth images from 2016, 2020, and 2024 at five locations that received social forestry approval in 2020. Data analysis was conducted using a geographic information system to observe changes in land cover area. The research results show that the approval of social forestry has a significant impact on land cover changes. The area of the forest has experienced a significant decline, especially in Forest Farmer Group (in Indonesia context called Kelompok Tani Hutan-KTH) Sungai Gulang, KTH Jaya Bersama, and KTH Semoga Jaya, which have been converted into coconut plantations. Meanwhile, KTH Usaha Makmur was able to maintain the forest stand, while KTH Sinar Tani completely converted its land into coconut plantations. These findings indicate that the implementation of social forestry needs to be balanced with stricter monitoring and guidance mechanisms to prevent wider forest degradation.